Cartographic representation of urban expansion on the vegetation cover and the basic design of Al-Nasiriyah city using GIS techniques - Jallab Mansiin, Samie; Al-Abdan, Rahim Hamid; Mutair, Saja Khairuddin (Al-Adab Journal, 2019)
The aim of this study is to use remote sensing techniques and geographic information systems to study and detect changes in the uses of urban land and green areas within the boundaries of the basic design and beyond the Nasiriyah civilization, based on the field study and basic designs prepared for the study area, as well as analysis and classification of satellite images taken by the moon Industrial Landsat (MSS) for the year 1970 and with (OLI) for the year 2016 for the purpose of monitoring changes in vegetation cover for the period 1970 to 2016. The production of digital maps to overcome urban land use on the common ground cover The classification of the city includes the category of barren land, agricultural land, urban land and marshes. The study showed that there were clear changes in the vegetation cover during the period from 1970 to 2016, which was the expansion of the type of urban land and the extension of its residential units at the expense of the agricultural land represented in the palm groves, which led to a decrease in area and especially after the events of 2003 It has resulted in a huge urban expansion at the expense of green areas. The total area of residential land during the year 2016 was (5631.2) hectares. Compared with (691.5)hectares in 1970 while the area of agricultural land decreased to (4866.9) hectares before it reached (6988.7) hectares in the area of (1511.9) hectares in 2016 of the total area of the city of Nasiriyah .